Stymulowanie rozwoju percepcji słuchowej małych dzieci z mózgowym porażeniem - Jakoniuk-Diallo, Anna; Kubiak, Hanna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
The text tackles the issue of stimulation of auditory perception in small children with cerebral palsy. Parents and specialists are able to use different methods to enhance the communication competence of small children which takes into consideration various needs of the child stemming from different areas of its development. In text there are some propositions of exercises, which could be done in everyday situations and which are attractive for small children; the aim of them is to develop auditory perception.